PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESA WISATA TANJUNG BALAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Harbimas, Abeltran; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tourism can provide opportunities for people to market their products, such as small businesses such as handicrafts, leather, woven goods, cosmetics and accessories, textiles, apparel, etc. can market themselves as much as possible thanks to tourism. A tourist village is an asset based on rural potential, including all its characteristics and attractions. From the background that has been described, the author is interested in analyzing tourism potential. Therefore, the author raises the title